Determinantes socioeconómicos de migración en México - Pick, James B.; Tellis, Glenda L.; Butler, Edgar W.; Pavgi, Suhas (El Colegio de México A.C., 1990)
This study examines the socioeconomic influence on migration frecuency and transitory movements in four Mexican regions. The analysis is based on date gathered from the Encuesta Mexicana de Fecundidad (Mexican Inquiry of Fertility) 1976-1977, considering the influences of their education, occupation, literacy, place of residence and fertility. The methods used for this analysis were regression and logistic regression. In the latter, the first three movement transitions were separated and individually analysed. The outcomes show a succession of socioeconomical influences based on the transitional state of the movement. For the 0-1 + transition the greatest effect is the place of residence, for the 1-2 + the migrant's occupation and for the 2-3 + the inconsistent effects of age and education. Specific effects are shown according to age and region